PENGARUH SELF-EFFICACYDAN MOTIVASI KERJA PADA KEPUASAN KERJA KARYAWAN HAPPY BALI TOUR & TRAVEL DENPASAR - Dewi Putu Eka Purnama; Dewi I Gusti Ayu Manuati (Faculty of Economics and Business Udayana University, 2015)
The aim of this study is to determine the influence of self-efficacy and work motivation on employee job satisfaction at Happy Bali Tour and Travel. The data was collected by using questionnaire consisting of a number of statements about self-efficacy, motivation and job satisfaction. This study used saturated sample, where the entire population was selected become sample which is consists of 82 employees. Data analysis techniques used in this research was multiple linear regression. The findings show that simultaneously, self-efficacy and work motivation has a significant effect on job satisfaction of employee. Additionally, self-efficacy and work motivation shows a positive impact on job satisfaction of Happy Bali Tour and Travel employee.